2020
DOI: 10.1007/s42452-020-03395-6
|View full text |Cite
|
Sign up to set email alerts
|

The interaction and mechanism of monoterpenes with tyramine receptor (SoTyrR) of rice weevil (Sitophilus oryzae)

Abstract: Rice weevils (Sitophilus oryzae) are pests that feed on grain products. One strategy employed in the safe pest management is the use of essential oils from plant materials as biopesticide. Monoterpene compounds, present in essential oils, are generally less acutely toxic than other conventional insecticides and are known to possess biopesticide activity against octopaminergic receptors (OAR). Tyramine receptor (TyrR) is a desired biopesticide target due to its absence in vertebrates and its role in insect's ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…This allosteric modulation of TAR1 was shown to interfere with the receptor expression and subsequently with the insect physiology and behavior [ 61 ]. Recent data have revealed that in silico prediction of the structural interaction between monoterpenes and S. oryzae TAR1 might provide new insights and possibly new molecules for TAR1-related pest control [ 95 ].…”
Section: Tar1: Insecticides Targetmentioning
confidence: 99%
“…This allosteric modulation of TAR1 was shown to interfere with the receptor expression and subsequently with the insect physiology and behavior [ 61 ]. Recent data have revealed that in silico prediction of the structural interaction between monoterpenes and S. oryzae TAR1 might provide new insights and possibly new molecules for TAR1-related pest control [ 95 ].…”
Section: Tar1: Insecticides Targetmentioning
confidence: 99%
“…Carene, pulegone, carvacrol, terpinolene, and thymol are determined to be top hits to more than one OAR/TAR. Four of these monoterpenes are also classified as top hits in the ensemble docking of SoTyrR in a separate study . On the other hand, top hits sabinene and camphene are unique to HvOctR; (+)-3-bromocamphor is unique to PxTyrR; and B-camphol is unique to SoTyrR.…”
Section: Resultsmentioning
confidence: 98%
“…Essential oil constituents such as monoterpenes have been shown to target arthropod proteins such as acetylcholinesterase (ACHE) and octopaminergic and tyraminergic receptors to induce neuromodulatory and neurotoxicity effects. Among plant secondary metabolites, monoterpenes have been widely studied and are considered as environmentally friendly and safe alternatives to conventional synthetic insecticides . Although observed to possess biological activities with OARs and TARs, monoterpenes exhibit different pharmacological effects in different insects.…”
Section: Introductionmentioning
confidence: 99%
“…Linalool may act on nAChRs and inhibit their current . Carvacrol and thymol may act on TA receptors and inhibit the binding of [ 3 H]-tyramine to TA receptors . Eugenol and α-terpineol inhibit the binding of [ 3 H]-octopamine to octopamine receptors .…”
Section: Pesticidal Mode Of Action Of Monoterpenesmentioning
confidence: 99%